1993
DOI: 10.1071/ar9931415
|View full text |Cite
|
Sign up to set email alerts
|

Variability in grain protein concentration of peas and lentils grown in Australia

Abstract: Protein and yield data were obtained from South Australian and Interstate pea and lentil variety trials conducted between 1986 and 1989, covering 94 pea and 58 lentil genotypes. Crude protein concentration varied significantly across sites and averaged 25.0% in peas and 24.4% in lentils. Protein concentration was not significantly correlated with yield at most individual sites. Minimum protein concentration in peas was 1.6% below the mean of three check cultivars in line RA155, while the maximum was 2.3% above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
7
13
0
Order By: Relevance
“…The negative correlation found between yield and protein concentration in faba bean and lentil agrees with reported similar trends in pea and lentil . In contrast, narrow‐leafed lupin had a unique positive correlation for these parameters owing to the high protein content of the high‐yielding, late‐maturing cultivars.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The negative correlation found between yield and protein concentration in faba bean and lentil agrees with reported similar trends in pea and lentil . In contrast, narrow‐leafed lupin had a unique positive correlation for these parameters owing to the high protein content of the high‐yielding, late‐maturing cultivars.…”
Section: Discussionsupporting
confidence: 87%
“…As suggested in previous studies on pea and lentil, 38 it is clear from our screening trial that protein concentration in all three species depended more on cultivar than on environment. Part of this stability is attributable to biological nitrogen fixation capacity, which allows the plants to maintain their nitrogen uptake regardless of variation in soil nitrogen supply.…”
Section: Protein Concentration and Nutritive Qualitysupporting
confidence: 83%
See 1 more Smart Citation
“…The increase or decrease in the protein contents is due to the activity of Allelochemicals. These findings are in close confirmatory to the studies reported earlier, in which minimum and maximum protein were 1.6 and 2.3% in peas (Stoddard et al, 1993). It is also reported in Table 1 that potassium contents increased from 25 to 75% concentrations as compared to control, while 100% showed a decrease in potassium content.…”
Section: Resultssupporting
confidence: 92%
“…Although it has earlier been reported that many legume crops such as pea and chickpea show a negative correlation between seed yield and protein content of seeds, others have shown an absence of correlation attributed to their capacity for biological nitrogen fixation (Frimpong et al, 2009;Jha, Arganosa, Tar'an, Diederichsen, & Warkentin, 2012;Stoddard, Marshall, & Ali, 1993). Many studies in faba bean have reported a similar absence of correlation (Picard, 1977;El-Sherbeeny & Robertson, 1992).…”
Section: Discussionmentioning
confidence: 98%